Waste Analysis Of Pasted Woven Production Process Using Lean Six Sigma Method - Agustina, Mega; Rochmoeljati, Rr. (Rekayasa, 2024)
This research was conducted in a company engaged in the production of cement bags which include pasted woven, pasted kraft, and sewn woven. Waste is still generated on the production floor throughout the pasted weaved manufacturing process. The essential waste that happens, including faults, waiting, Environmental, Health, and Safety, as well as other problems that cause the lead time to be too lengthy, namely 1430 minutes. The goal of this study is to assess the degree of waste that happens by calculating Defects Per Million Opportunities and the sigma level, as well as to make recommendations for improvement. The research results show that the reduction in lead time for waste of non-value-added defects in the pasted woven production process, which was originally worth 1430 minutes, can be reduced to 1365 minutes by reducing activities in the form of a 65-minute delay, thereby reducing cycle time in the pasted woven production process. The average DPMO value was 36898 at a sigma level of 3.284. Proposed modifications to decrease waste are analyzed using Failure Mode and Effect Analysis and Risk Priority Number values to identify the sources of waste. Recommendations for companies provide training to operators to avoid human error, inspect raw materials before entering the production process and periodically control the condition of machines.